Efficacy of N-Acetylcysteine in Idiopathic Pulmonary Fibrosis: A Systematic Review and Meta-Analysis. Issue 19 (May 2016) - Sun, Tong; Liu, Jing; Zhao, De Wei
Abstract : Abstract: There are a number of conflicting reports describing the clinical outcomes of using N -acetylcysteine for the treatment of idiopathic pulmonary fibrosis. We have, therefore, performed a meta-analysis to evaluate the efficacy of N -acetylcysteine, compared with control, for the treatment of idiopathic pulmonary fibrosis. Original controlled clinical trials evaluating the efficacy of N -acetylcysteine for the treatment of idiopathic pulmonary fibrosis were included in the analysis. Searches for relevant articles were carried out in July 2014 by 2 independent researchers using PubMed, Embase, Cochrane Central, and Google Scholar. Change in forced vital capacity, change in percentage of predicted vital capacity, change in percentage of predicted carbon monoxide diffusing capacity, changes in 6 minutes walking test distance, rate of adverse events, and rate of death were expressed as outcomes using RevMan 5.0.1. Five trials, with a total of 564 patients, were included in this meta-analysis. The meta-analysis showed that the control group had significant decreases in percentage of predicted vital capacity (standardized mean difference [SMD] = 0.37; 95% confidence interval [CI]: 0.13 to −0.62; P = 0.003) and 6 minutes walking test distance (SMD = 0.25; 95% CI: 0.02–0.48; P = 0.04). There were no statistically significant differences in forced vital capacity (SMD = 0.07; 95% CI: −0.13–0.27; P = 0.52), percentage of predicted carbon monoxide diffusing capacity (SMD = 0.12; 95% CI: −0.06–0.30; P = 0.18), rates of adverse events (odd ratio = 4.50; 95% CI: 0.19–106.41; P = 0.35), or death rates (odd ratio = 1.79; 95% CI: 0.3–5.12; P = 0.28) between the N -acetylcysteine group and the control group. N -Acetylcysteine was found to have a significant effect only on decreases in percentage of predicted vital capacity and 6 minutes walking test distance. N -acetylcysteine showed no beneficial effect on changes in forced vital capacity, changes in predicted carbon monoxide diffusing capacity, rates of adverse events, or death rates.